Robust Controller LMI for helicopter with two degrees of freedom - Oscar Iván Higuera-Martínez; Juan Mauricio Salamanca (Ingeniería Investigación y Desarrollo, 2015)
This article presents the design of a robust H∞ controller using techniques of linear matrix inequalities (LMIs) for controlling the position of Pitch and Yaw in a helicopter. Designing a FF + LMI controller is presented for stabilizing the system, and further the design of LMI + FF + integrator controller is performed to make the tracking error equal to zero. Thereafter the results of simulations are showed on the nonlinear system model and a comparison with FF+LQR and FF+LQR+I which were developed by device manufacturers.